Tourisme et pauvreté dans les petites îles indépendantes en développement : l’exemple de Sainte-Lucie (Petites Antilles) - Dominique Augier (Études Caribéennes)
The objective of this study is to analyse the impacts and limitations of attempts to combat poverty using tourism through a case study in the village of Anse-la-Raye, in St. Lucia.Since its independence in 1979, St. Lucia has attempted to diversify the economic structure it inherited from its colonial past, in particular developing alternative sources of revenue. Initially there was some success with the clothing industry and tourism, which emerged as viable business activities outside of agricultural exports.At the end of the 1980s, the country had reached a growth which was considered reasonable. Of all the states of CARICOM, St. Lucia has moreover experienced the greatest economic growth. Banana exports have contributed significantly to these results, and new sectors have led to the creation of jobs and income to supplement export income.But like all Small Island Developing States (SIDS), St. Lucia is characterized by vulnerability to natural disasters and external economic shocks. Two major sectors of the economy have weakened in recent years (agriculture and industry), resulting in an increase in poverty in St. Lucia despite favourable outcomes in the tourism sector, which became the primary pillar of the island.In the context of low economic growth the government and social partners gathered together to identify policies and accelerate economic growth in St. Lucia. Three main themes were identified: Increasing local production; reducing crime and reducing poverty. In this context, the government launched several strategies to combat poverty including assistance for the development of tourism.The study focuses on the village of Anse-la-Raye and the experiences of pro-poor tourism that was developed in 2000: Anse-la-Raye Seafood Friday, a kind of festival that allows visitors to taste the seafood on Fridays. Has this festival really had an impact on the poor of the community of Anse-la-Raye? Is it viable? And what is its future?